Older than they look: Cryptic recycled xenotime on detrital zircon - Dröllner, Maximilian; Barham, Milo; Kirkland, Christopher; Roberts, M.P. (2023)
Dating of xenotime outgrowths (XOs) has been used to obtain depositional age constraints on sedimentary sequences devoid of volcanic tuffs and biostratigraphically useful fossils (i.e., most of Earth history). Here, we present geochronological and geochemical data from XOs on detrital zircon from the Early Cretaceous Broome Sandstone, NW Australia. Ages of XOs predate the palynologically constrained deposition of the Broome Sandstone by at least 150 m.y., suggesting that these XOs were detrital and transported together with the zircon to which they are attached. This finding contrasts with the general assumption that XOs are principally authigenic phases. Integration of geochronology and geochemistry links Broome Sandstone XOs to intermediate geological events in the sediment source area. These results emphasize the importance of evaluating a potential detrital origin for XOs because sedimentary transport does not appear to universally destroy nor liberate them from their zircon substrate. Despite this, the study of XOs provides an important means to reconstruct complexities of source-to-sink sediment histories, including intermediate storage and overprinting, e.g., during diagenetic, metamorphic, hydrothermal, and igneous activity. Such information is critical for more holistic geological reconstructions but is not retained within the most applied provenance tool (detrital zircon).